The Landing Error Scoring System (LESS) Is a valid and reliable clinical assessment tool of jump-landing biomechanics: The JUMP-ACL study - Padua, Darin A; Marshall, Stephen W; Boling, Michelle C; Thigpen, Charles A; Garrett, Jr, William E; Beutler, Anthony I (The American journal of sports medicine, 2009)
Anterior cruciate ligament injuries are common in athletes and have serious sequelae. A valid clinical tool that reliably identifies individuals at an increased risk for ACL injury would be highly useful for screening sports teams, because individuals identified as "high-risk" could then be provided with intensive prevention programs. A clinical screening tool (the Landing Error Scoring System, or LESS) will reliably identify subjects with potentially high-risk biomechanics. Cohort study (Diagnosis); Level of evidence, 2. A jump-landing-rebound task was used. Off-the-shelf camcorders recorded frontal and sagittal plane views of the subject performing the task. The LESS was scored from replay of this video. Three-dimensional lower extremity kinematics and kinetics were also collected and used as the gold standard against which the validity of the LESS was assessed. Three trials of the jump-landing task were collected for 2691 subjects. Kinematic and kinetic measures were compared across LESS score quartiles using 1-way analysis of variance; LESS quartiles were compared across genders using the chi-square test. The LESS scores from a subset of 50 subjects were rescored to determine intrarater and interrater reliability. Subjects with high LESS scores (poor jump-landing technique) displayed significantly different lower extremity kinematics and kinetics compared with subjects with low LESS scores (excellent jump-landing technique). Women had higher (worse) LESS scores than men. Intrarater and interrater reliability of the LESS ranged from good to excellent. The LESS is a valid and reliable tool for identifying potentially high-risk movement patterns during a jump-landing task.